TEKTONOSTRATIGRAFI BUSUR BANDA LUAR DENGAN REFERENSI BAGIAN BARAT TIMOR LESTE DAN BAGIAN TIMUR PULAU SERAM - Syaiful Bachri (Jurnal Geologi dan Sumberdaya Mineral, 2011)
Timor and Seram Islands are parts of the Banda Outer Arc which represent a collision zone between Northwest Shelf of Australia and the subduction system of the pre-collisional Banda Arc. Consequently, the rock units in this region can be catagorized into three different tectonostratigraphic sequences which represent differents origins. The first sequence is called the para-autochtonous sequence which is derived from NW Shelf of Australia, and is still lying on its basement, since the basement also moving northwards together with its sediment cover. The second sequence is pre-collisional Banda forearc sequence, and is called the allochtonous sequence, which overthrust on to the para-autochtonous sequence forming nappe structures. The third sequence is autochtonous sequence which is unconformably overlying the para-autochtonous and allochtonous sequences. The Bobonaro Complex in western part of Timor Leste can be compared with the Salas Complex in the Seram Island which represent the oldest aotochtonous unit forming olistostrom deposits. On the other hand, ophiolites in western part of Timor Leste can be compared with ultramafics rocks in eastern part of Seram Island, forming the basement of the allochtonous sequence. Meanwhile, the Lolotoi Complex in western part of Timor Leste can be correlated with the Kobipoto Complex in estern part of Seram Island, which form the basement of the para-autochtonous sequence.Key words: Para-autochtonous sequence, allochtonous sequence, autochtonous sequence, Banda outer arc, wester part of Timor Leste, Eastern part of Seram Island